Skrining Aktivitas Antimalaria Beberapa Tanaman Indonesia Hasil Eksplorasi Dari Hutan Raya Cangar, Batu-Malang, Jawa Timur - Achmad Fuad Hafid; Nike Puliansari; Nur Suci Lestari; Lidya Tumewu; Abdul Rahman; Aty Widyawaruyanti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2016)
Background: Malaria is the most important parasitic disease. Malaria control which depends on specific chemotherapy now complicated by resistance of Plasmodium falciparum to most commonly available antimalarial drug. Such situation has heralded the need for alternative antimalarial therapy. Objective: This research aim was to find new antimalarial candidates from some Indonesia plants collected from Cangar National Forest, Batu-Malang, East Java. Methods: Eleven samples of leaves and stem extracts were screened against Plasmodium falciparum 3D7 culture which maintained in RPMI-1640 Medium. Samples tested in concentration of 0.01, 0.1, 1, 10 and 100 µg/ml. Probit analysis was used to determine IC50. Results: In vitro antimalarial activity revealed that only three crude extracts samples from Fraxinus griffithi stem extract, Piper sulcatum leaves extract and Eucalyptus globulus stem extract had good antimalarial activity with IC50 value of 0.33, 0.20 and 0.55 µg/ml, respectively. Conclusions: Fraxinus griffithi stem extract, Piper sulcatum leaves extract and Eucalyptus globulus stem extract might be a good candidate for antimalarial natural product resources.